Nutrient Consumption by Chenin Blanc grown in Sand Culture and Seasonal Changes in the Chemical Composition of Leaf Blades and Petioles - Conradie, W. J. (South African Journal of Enology and Viticulture, 2017)
The seasonal utilization of N, P, K, Ca and Mg by the various aerial and underground organs of bearing Chenin blanc/99R grown in sand culture under South African climatic conditions was tabulated. During the production of one ton of grapes, the bunches accumulated 1,39; 0,25; 1,98; 0,17 and 0,09 kg N, P, K, Ca and Mg respectively, the permanent parts of the vine accumulated a further 0,73; 0,10; 0,19; 0,14 and 0,08 kg, and the vegetative growth (leaves plus prunings) accumulated 1,77; 0,37; 0,88; 1,70 and 0,43 kg. Appreciable seasonal changes were found in the chemical composition of both leaf blades and petioles. The petioles showed a reasonably stable composition during the month following bloom verifying the results of other workers, and samples for analyses should, therefore, be collected at this stage. However, the nutrient concentrations in the leaf blades remained unstable. The nutrient export figures obtained in this experiment may be used in conjunction with occasional petiole analyses as a basis for fertilizer recommendations. However, in the case of petiole analyses reliable norms are still lacking.